English as a We-Code: form and Function of English in Facebook Status Updates of Non-Native Female and Male Users - Dąbrowska, Marta (Research in Language, 2019)
The English language has featured markedly as a popular language of computer-mediated communication, and notably of Facebook posts, written not only by native or second language speakers, but also users of English as a foreign language. The aim of this paper is to investigate the frequency, form and function of English language Facebook profile updates of 110 (55 women and 55 men) users of English representing 41 European, Asian, African and Latin American countries belonging to the Expanding Circle. Approached from the point of view of the code choice as well as the users’ gender, and supported by an online survey data, the study analyses in detail the form of the updates in connection with gender preferences and identifies language contexts and functions users choose to express themselves in English as opposed to their native tongue, thereby demonstrating the role of English as a we-code in a social networking service.